Hemodynamic recovery after hypovolemic shock with lactated Ringer's and keratin resuscitation fluid (KRF), a novel colloid - Nuñez, Fiesky A.; Callahan, Michael F.; Trach, Simon Martin; Burnett, Luke R.; Kislukhin, Victor; Smith, Thomas L.; Van Dyke, Mark (Artificial cells, nanomedicine, and biotechnology, 2013)
Death after severe hemorrhage remains an important cause of mortality in people under 50 years of age. Keratin resuscitation fluid (KRF) is a novel resuscitation solution made from keratin protein that may restore cardiovascular stability. This postulate was tested in rats that were exsanguinated to 40% of their blood volume. Test groups received either low or high volume resuscitation with either KRF or lactated Ringer's solution. KRF low volume was more effective than LR in recovering cardiac function, blood pressure and blood chemistry. Furthermore, in contrast to LR-treated rats, KRF-treated rats exhibited vital signs that resembled normal controls at 1-week.
Gesehen am 29.11.2021